Implementation of Active Learning Learning Model Using the Google Classroom Application in Comparative Literature Courses - Amrizal Amrizal; Amril Canrhas; Fina Hiasa (BAHASTRA, 2021)
This study aims to determine how the implementation of the Active Learning learning model assisted by the Google Classroom application in the Comparative Literature course can improve the learning quality of the fifth-semester students of the Indonesian Language Education Study Program, FKIP, Bengkulu University. The Research and Development (R&D) method is a method used in this study with the aim of testing whether the implementation of the Active Learning learning model using the Google Classroom application can improve the quality of learning. The implementation that you want to prove can be seen from several stages carried out in this study, namely preliminary studies, development stages, product testing, and product evaluation. Product testing activities in the form of tests in the form of essays and multiple-choice using Active Learning assisted by the Google Classroom application showed good learning outcomes where the average score obtained by trainee students in comparative literature was 85.5 from a maximum average score of 100 points. This shows that the application of the active learning model assisted by Google Classroom in the Comparative Literature course makes the learning process effective and enjoyable for students.